(untitled) (Documentos y Aportes en Administración Pública y Gestion Estatal, 2025)
The modernization of the State refers to the need to establish transparency in public management. This requires open governments capable of offering access to information, accountability and electronic government. The Crime and Violence Observatory (CVO), created in 2019, has positioned itself as a cardinal instrument for public security in the province of Río Negro, through field work and the use of technological tools functional to the management transparency. So this work aims to describe, through a documentary analysis, the different actions and tasks implemented by the ODV since its creation. The results collected position the ODV as a regional example of modernization of the State for the transparency of public management in matters of security.